Gold nanoparticle-based colorimetric biosensors. Issue 1 (6th December 2017) - Aldewachi, H.; Chalati, T.; Woodroofe, M. N.; Bricklebank, N.; Sharrack, B.; Gardiner, P.
Abstract : Gold nanoparticles (AuNPs) provide excellent platforms for the development of colorimetric biosensors as they can be easily functionalised, displaying different colours depending on their size, shape and state of aggregation. Abstract : Gold nanoparticles (AuNPs) provide excellent platforms for the development of colorimetric biosensors as they can be easily functionalised, displaying different colours depending on their size, shape and state of aggregation. In the last decade, a variety of biosensors have been developed to exploit the extent of colour changes as nano-particles (NPs) either aggregate or disperse, in the presence of analytes. Of critical importance to the design of these methods is that the behaviour of the systems has to be reproducible and predictable. Much has been accomplished in understanding the interactions between a variety of substrates and AuNPs, and how these interactions can be harnessed as colorimetric reporters in biosensors. However, despite these developments, only a few biosensors have been used in practice for the detection of analytes in biological samples. The transition from proof of concept to market biosensors requires extensive long-term reliability and shelf life testing, and modification of protocols and design features to make them safe and easy to use by the population at large. Developments in the next decade will see the adoption of user friendly biosensors for point-of-care and medical diagnosis as innovations are brought to improve the analytical performances and usability of the current designs. This review discusses the mechanisms, strategies, recent advances and perspectives for the use of AuNPs as colorimetric biosensors.